A cultura escrita nos anos iniciais do ensino fundamental: implicações pedagógicas da Teoria Histórico- Cultural - Lugle, Andreia Maria Cavaminami [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The object of study of this doctoral thesis is the relations established between written culture and the appropriation of such language during the early years of Elementary School. My general objective is to understand the role written culture plays in the appropriation of written language during the early years of Elementary School, and reflect over its pedagogical implications, according to cultural-historical and Bakhtin's theories. I enumerate as specific objectives: a) to identify practices aiming the development of reading and writing in classes ranging from first to fifth grade of elementary school; b) to verify the concept elementary school students attribute to reading and writing; c) to understand how cultural-historical and Bakhtin's theories contribute to the comprehension of the written language appropriation process.The investigation was performed in a County Public School in the city of Londrina, Paraná, between the months of August/2013 and November/2014. The data collection instruments were classroom observations, interviews with 81 students from first to fifth grade of elementary school, and pedagogical actions developed with such students. Results revealed that the teaching promoted by schools concerning the appropriation of reading and writing is still guided by the acts of decoding and encoding, of mastering the relationship between sound and letter. The presence of written culture is restricted to textbooks, or to teachers' expository information, which directly limits the appropriation of written language as a cultural instrument, as well as the comprehension of its social function by students. As of these findings, I searched for indications regarding how to organize adequate conditions to the appropriation of written language substantiated on cultural-historical and Bakhtin's theories, and performed some procedures with such classes thereafter. I found possible a pedagogical practice that inserts students...

O objeto de estudo desta tese são as relações estabelecidas entre a cultura escrita e a apropriação da linguagem escrita nos anos iniciais do ensino fundamental. Apresento como objetivo geral compreender o lugar que a cultura escrita ocupa na apropriação da linguagem escrita nos anos iniciais do ensino fundamental e refletir sobre suas implicações pedagógicas segundo as teorias histórico-cultural e bakhtiniana. Elenco como objetivos específicos: a) identificar as práticas destinadas ao desenvolvimento da leitura e da escrita em turmas do 1º ao 5º ano do ensino fundamental; b) verificar o conceito que os estudantes do ensino fundamental atribuem à leitura e à escrita; c) entender como as teorias histórico-cultural e bakhtiniana contribuem para a compreensão do processo de apropriação da linguagem escrita. A investigação foi realizada em uma escola municipal em Londrina/Paraná, entre os meses de agosto de 2013 e novembro de 2014. Os instrumentos de coleta de dados foram: observação em sala de aula, entrevistas com 81 alunos do 1º ao 5º ano do ensino fundamental e ações desenvolvidas com os alunos em sala de aula. Os resultados revelaram que o ensino promovido pela escola na apresentação da leitura e da escrita ainda é pautado pelos atos de decodificação e codificação, de domínio da relação entre o som e a letra. A presença da cultura escrita é restrita aos livros didáticos ou às informações expositivas dos professores, o que limita diretamente a apropriação da linguagem escrita pelos alunos como instrumento cultural, bem como a compreensão da sua função social. A partir destas constatações, busquei indicações sobre como organizar as condições adequadas à apropriação da linguagem escrita fundamentadas na teoria históricocultural e bakhtiniana e realizei, então, algumas ações com as turmas. Constatei ser possível uma prática pedagógica que insere os alunos na atividade...
Keywords: Educação; Ensino fundamental; Escrita; Leitura; Education